2015
DOI: 10.4172/2153-2435.1000422
|View full text |Cite
|
Sign up to set email alerts
|

Blood Glucose Lowering Effect and Safety of the Aqueous Leaf Extracts of Zanha africana

Abstract: Zanha africana has been used traditionally to manage many diseases including diabetes, however, its antidiabetic activity and safety is not well evaluated. The aim of this study was to determine in vivo hypoglycemic activity and safety of the aqueous leaf extracts of this plant in male Swiss white albino mice. The antidiabetic activity was screened in alloxan induced diabetic mice using oral and intraperitoneal routes. The safety of the extract was studied in mice that were orally and intraperitoneally adminis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Several studies have been reported that, different biochemical have different mechanism to regulate and decrease blood glucose level [48]. Flavonoids either mimic as insulin or regulate the expression of enzymes involved in carbohydrate metabolism path way which enhance glucose uptake in tissues [49].…”
Section: Impact Of Extract On the Glycemic Regulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have been reported that, different biochemical have different mechanism to regulate and decrease blood glucose level [48]. Flavonoids either mimic as insulin or regulate the expression of enzymes involved in carbohydrate metabolism path way which enhance glucose uptake in tissues [49].…”
Section: Impact Of Extract On the Glycemic Regulationmentioning
confidence: 99%
“…Tannins are associated with glucose uptake from blood to muscles and other tissues by inducing translocation of the glucose transporter GLUT-4 and phosphorylation of the insulin receptors [51]. It has been also reported that saponins reduce serum glucose levels in old age diabetic patients [48,52]. It has been reported mushroom belongs to genus Pleurotus possess antidiabetic activity [47].…”
Section: Impact Of Extract On the Glycemic Regulationmentioning
confidence: 99%